Kurdi, Mária. Nemzeti önszemlélet a mai ír drámában (1960-1990) [National Self-Observation in Contemporary Irish Drama 1960-1990]. Budapest: Akadémiai, 1999. 228 pp. - Mesterházi, Márton (FOCUS: Papers in English Literary and Cultural Studies, 2024)
As Maria Kurdi’s monograph National Self-Observation in Contemporary Irish Drama was published three years ago, I think the best way to draw, or rather refresh professional attention to it is to present a short reader’s report.